The Impact of Telemonitoring and Telehealth Coaching on Depression, Anxiety, and Stress Scales in Overweight and Obese Individuals: A Pilot Randomized Controlled Trial - Noura M. S. Eid; Ebtisam A. Al-Ofi; Sumia Enani; Rana H. Mosli; Raneem R. Saqr; Karimah M. Qutah; Sara M. S. Eid (Obesities)
(1) Background: The literature has demonstrated several pathways that link obesity with stress. Thus, new approaches to weight management programs must also integrate health coaching and telemonitoring for overall health and wellbeing. This study aimed to measure stress, anxiety, and depression scales (DASS-21) in overweight and obese participants who joined a pilot randomized controlled trial (RCT) and the association between changes in DASS-21 scores and changes in anthropometric measures. (2) Methods: Fifty participants were enrolled in a randomized controlled trial and divided into two groups: the intervention group, which received a hypocaloric diet remotely, weekly telemonitoring, and monthly telehealth coaching, and the control group, which only followed a hypocaloric diet without any support. The Arabic version of the Depression Anxiety Stress Scales (DASS-21) was used. (3) Results: The data reveal that participants from the intervention group exhibited a significant decrease in the anxiety scale after 3 months compared with the control group. In addition, the correlations between depression, anxiety, stress, and all anthropometric measures in the intervention group showed a moderately significant positive correlation between changes in waist circumference and depression. (4) Conclusions: The findings confirm that integrating health coaching and telemonitoring can improve wellbeing and weight loss.